Integration of Science, Technology, Engineering and Mathematics: Is this Curricular Revolution really possible in France? - Lebeaume, Joël (Design and Technology Education: An International Journal, 2011)
The French school system is a subjects-centred curriculum from the beginning of 1960s. This deep-rooted organisation tends to block the several attempts made to integrate the teaching of scientific school subjects. From an historical point of view, this paper describes the curricular system and the issue of its current change. It focuses on the main issue about separation or integration of these subjects in secondary school.